How would an accused / defence successfully argue non-pathological criminal incapacity or alternative defences, namely in the battered wife / partner syndrome? - Carstens, Pieter Albert, 1960- (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.